Pengaruh Corporate Governance Perception Index Terhadap Tingkat Financial Distress - Mayang Murni; Lily Karlina Nasution (Jurnal Penelitian Ekonomi Akuntansi, 2024)
Banking companies have a role as an intermediary institution because of the foundation in building a country's economy. Banking companies that implement good Corporate Governance practices tend to be free from bad things like financial distress. This research aims to observe the influence of Corporate Governance Perception Index on Level of Financial Distress in BUMN Banking Companies form 2018-2023. . The data used is secondary data from the financial reports of state-owned banking companies and was analyzed using linear regressions. The result showed that Corporate Governance Perception Index has a influence on Financial Distress with a value that tend to small 5,9% with a minus contant, its means that the effect of implementing good Good Corporate Governance does not greatly affect the level of Financial Distress in BUMN Banking Companies in Indonesia. This is a limitation in the study, namely the object of research on BUMN companies in Indonesia, where the majority of ownership by the Government so that control and assurance of the continuity of a company depends on Government policies and public interests, so as not to worry about things like the level of financial distress. Based on the limitations, one suggestion that can be given is to replace the object of research on private companies included in the ranking of the Indonesian Institute for Corporate Governance or the ASEAN Corporate Governance Scorecard, as well as adding other fundamental indicators in assessing the level of Financial Distress